Chagas cardiomyopathy and heart failure : from epidemiology to treatment - Santos, Érico (2021)
© 2020 Sociedade Portuguesa de Cardiologia. Published by Elsevier España, S.L.U. This is an open access article under the CC-BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).